2020
DOI: 10.1371/journal.pone.0227224
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and in vivo evaluation of imidazo[2,1-b]thiazole-5-carboxamide anti-tuberculosis compounds

Abstract: The imidazo[2,1-b]thiazole-5-carboxamides (ITAs) are a promising class of anti-tuberculosis agents shown to have potent activity in vitro and to target QcrB, a key component of the mycobacterial cytochrome bcc-aa3 super complex critical for the electron transport chain. Herein we report the intracellular macrophage potency of nine diverse ITA analogs with MIC values ranging from 0.0625-2.5 μM and mono-drug resistant potency ranging from 0.0017 to 7 μM. The in vitro ADME properties (protein binding, CaCo-2, hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
(89 reference statements)
0
22
0
Order By: Relevance
“…In particular, the imidazo [1,2-a] pyridine amides (IPAs) class is surprisingly highly selective to mycobacteria [ 48 , 50 ], and the most advanced derivatives showed MICs in the nanomolar range. The discovery of Q203 (Telacebec, Figure 8 ) [ 51 ], the most advanced compound of this class, has prompted many to lead optimization programs around the IPA scaffold providing elaborated SARs: 6- or 7-Cl groups at the R 2 position enhance both the activity and the metabolic stability with respect to the unsubstituted compounds [ 52 , 53 , 54 ]; the ethyl group at R 1 appears to be the most favorable [ 52 , 53 , 54 ]; a lipophilic side chain is pivotal for the activity, regardless of chain length and linearity [ 52 ]; the substituted N -benzyl group at the side chain is important but not critical for the activity [ 53 , 54 , 55 , 56 , 57 ]; 4-trifluoromethoxy-phenyl-piperidino group is the best one at the side chain, but can be replaced by other nitrogen heterocycles to improve PK properties [ 55 , 58 ]; generally, scaffold switching is not a good option since that of the imidazo [1,2-a] pyridine-3-carboxamides is optimal for potency and ADME properties [ 59 ], but there are a few exceptions [ 60 , 61 , 62 ]; the presence of -NH in the carboxamide group at 3 is critical for the activity, as well as the carbonyl group [ 53 , 54 ]; switching the position of the carboxamide from 3 to 2 results in less effective derivatives. …”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the imidazo [1,2-a] pyridine amides (IPAs) class is surprisingly highly selective to mycobacteria [ 48 , 50 ], and the most advanced derivatives showed MICs in the nanomolar range. The discovery of Q203 (Telacebec, Figure 8 ) [ 51 ], the most advanced compound of this class, has prompted many to lead optimization programs around the IPA scaffold providing elaborated SARs: 6- or 7-Cl groups at the R 2 position enhance both the activity and the metabolic stability with respect to the unsubstituted compounds [ 52 , 53 , 54 ]; the ethyl group at R 1 appears to be the most favorable [ 52 , 53 , 54 ]; a lipophilic side chain is pivotal for the activity, regardless of chain length and linearity [ 52 ]; the substituted N -benzyl group at the side chain is important but not critical for the activity [ 53 , 54 , 55 , 56 , 57 ]; 4-trifluoromethoxy-phenyl-piperidino group is the best one at the side chain, but can be replaced by other nitrogen heterocycles to improve PK properties [ 55 , 58 ]; generally, scaffold switching is not a good option since that of the imidazo [1,2-a] pyridine-3-carboxamides is optimal for potency and ADME properties [ 59 ], but there are a few exceptions [ 60 , 61 , 62 ]; the presence of -NH in the carboxamide group at 3 is critical for the activity, as well as the carbonyl group [ 53 , 54 ]; switching the position of the carboxamide from 3 to 2 results in less effective derivatives. …”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
“…generally, scaffold switching is not a good option since that of the imidazo [1,2-a] pyridine-3-carboxamides is optimal for potency and ADME properties [ 59 ], but there are a few exceptions [ 60 , 61 , 62 ];…”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
“…A recent study demonstrated its good in vitro ADME properties including, protein binding, CaCo-2, human microsomal stability, and CYP450 inhibition. They also demonstrated the good efficacy of a tool compound, ND-11543, in the murine TB infection model (Moraski et al, 2020).…”
mentioning
confidence: 95%
“…Additionally, cross-resistance studies with strains harbouring QcrB mutations and dose-response studies in a M. tb strain without Cyt-bd oxidase indicate that these compounds target QcrB [143]. This series is promising for its tolerability and good oral bioavailability in mice [126].…”
Section: Inhibitors Of the Cyt-bcc-aa3 Complexmentioning
confidence: 97%
“…Structurally similar to the IPs, the pyrazolopyridine carboxamide series were designed as novel anti-tubercular agents through a scaffold hopping strategy [150,151] Several promising hits belonging to the chemical class of imidazopyridines (IPs) have been identified in independent screening programs [12,75,[137][138][139]. Extensive efforts have been undertaken to optimise and to explore the SAR of this scaffold [126,[140][141][142][143]. To date, the most advanced QcrB inhibitor is Q203, an IP derivative in Phase 2 clinical trials.…”
Section: Inhibitors Of the Cyt-bcc-aa3 Complexmentioning
confidence: 99%